FAKTOR PENDORONG KONVERSI LAHAN SAWAH DI KABUPATEN TANAH DATAR - GEMI RAHIM; ratna wilis (JURNAL BUANA, 2022)
The purpose of this study was to determine changes in the use of paddy fields and the driving factors for the conversion of paddy fields in Tanah Datar Regency. This research is a descriptive quantitative research. The sampling technique used in this study is the Nonprobability Sampling technique with the Quota Sampling method. Data collection techniques using questionnaires and processing Google Earth satellite images with overlay techniques. The data analysis technique used multiple linear regression analysis and geographic information system (GIS). The results showed that: (1) There was a decrease in the area of ​​rice fields from 2010 to 2020 by 723.4 ha in Tanah Datar Regency. (2) Economic pressure, selling price of land, perception of the profession of farmers, the existence of inheritance law, and the culture of wandering simultaneously have positive and significant effects on the conversion of paddy fields in Tanah Datar Regency. (3) Economic pressure and the existence of inheritance law have a positive effect on the conversion of paddy fields in Tanah Datar Regency. Meanwhile, the selling price of land, the perception of the profession of farmers, and the culture of wandering do not have a positive effect on the conversion of paddy fields in Tanah Datar Regency.